Automatización y control de un sistema de calefacción, ventilación y aire acondicionado (HVAC) mediante la construcción de un prototipo análogo a un área de producción farmacéutica utilizado para el desarrollo de habilidades educativas - Herrera Molina, Jineth Melissa; Moreno Jiménez, Harrison Yovany (Universidad Antonio Nariño, 2023)
This document details the process of design, development and implementation of a prototype HVAC system in the area of a pharmaceutical plant. In this project, measuring instruments were used and the variables temperature, humidity and differential pressure were controlled through the programming of the CPU NoDE MCU ESP32 processor to ensure the correct operation of the system.